Some features of seeds and clonal reproduction Stevia Rebaudiana Bertony in conditions of Daghestan - Z. M. Asadulaev; Z. K. Gadzhieva (Юг России: экология, развитие, 2015)
In article are presented adaptive and reproductive potential’s studies of Stevia rebaudiana Bertony in conditions of Daghestan. The features of seeds and clonal reproduction, keeping of the uterine plants at the winter and new methods of production’s increasing are installed.